The Differences on the Effect of Low Impact and High Impact Aerobic Exercise Against The Decreasing of Total Cholesterol Levels on Women - Ruhardi, Rudi; Sugiyanto, S; Hidayatullah, M. Furqon (Journal of Education, Health and Sport, 2018)
Background: The purpose of this research was to know and to analyze (1) the differences of intensity effect between low impact aerobic and high impact aerobic on the decreasing of total blood cholesterol levels, (2) the decreasing differences of total blood cholesterol levels between early adult women and middle adult women, (3) the interaction effects between the intensity of aerobic exercise and adulthood women on the decrease of total blood cholesterol levels. Subject and Method: This research employed an experimental method consisting of independent variables and dependen variable. The research used experimental method with 2x2 factorial design. The population was all of members of Community Healthy Ambassador of Nursing Center Budinersalindo Wonogiri. Result: The results of two ways anava test obtained F count value calculated on aerobic exercise intensity group amount 23.88 , F count value > F table (23.88 > 3.39 ), it means that there was a difference of total cholesterol level in intensity group of low impact and high impact aerobic exercise. The results of the test in the age group of adult women obtained the F count value amount 10.45, the F count value > F table (10.45 > 3.39 ), it means that there was a difference in total cholesterol levels in the age group of early adult women and middle adult women. The result of interaction test (A X B) obtained F count value amount 1.86, F count < F table (1.86 < 3.39), it means that there was no interaction effect between aerobic exercise and age group. Conclution: The conclusions of this research were (1) there were differences effects between intensity of low impact and high impact aerobic exercise toward the decrease of total blood cholesterol level; the low impact aerobic had better decrease than the high impact aerobic had, (2) there were differences of the decrease of total blood cholesterol levels between early adult women and middle adult women; the middle adult women had better decrease than the early adult women had (3) there was no interaction effect between aerobic exercise and adult women toward the decrease of total blood cholesterol levels